Hydrolysis of Element (White) Phosphorus under the Action of Heterometallic Cubane-Type Cluster Mo3PdS4 - Kuchkaev, Airat M.; Shmelev, Nikita Y.; Kuchkaev, Aidar M.; Sukhov, Aleksandr V.; Babaev, Vasily M.; Khayarov, Khasan R.; Gushchin, Artem L.; Sokolov, Maxim N.; Sinyashin, Oleg G.; Yakhvarov, Dmitry G. (Molecules (Basel, Switzerland), 2021)
Reaction of heterometallic cubane-type cluster complexes—[Mo3{Pd(dba)}S4Cl3(dbbpy)3]PF6, [Mo3{Pd(tu)}S4Cl3(dbbpy)3]Cl and [Mo3{Pd(dba)}S4(acac)3(py)3]PF6, where dba—dibenzylideneacetone, dbbpy—4,4′-di-tert-butyl-2,2′-bipyridine, tu—thiourea, acac—acetylacetonate, py—pyridine, with white phosphorus (P4) in the presence of water leads to the formation of phosphorous acid H3PO3 as the major product. The crucial role of the Pd atom in the cluster core Mo3PdS4 has been established in the hydrolytic activation of P4 molecule. The main intermediate of the process, the cluster complex [Mo3{PdP(OH)3}S4Cl3(dbbpy)3]+ with coordinated P(OH)3 molecule and phosphine PH3, have been detected by 31P NMR spectroscopy in the reaction mixture.